Trace element, oxidant, and antioxidant enzyme values in blood of children with refractory epilepsy. (1st March 2014) - Saad, Khaled; Hammad, Emad; Hassan, Asmaa F.; Badry, Reda
<x xml:space="preserve">Abstract</x> Purpose: The aim of this study is to evaluate the serum levels of some trace elements, oxidants, and antioxidants in children with intractable epilepsy compared to healthy children. Patients and Methods: In a case–control study, 40 children (24 males and 16 females) suffering from refractory generalized epileptic seizures were compared with 40 sex- and age-matched healthy children serve as a control group. Serum selenium (Se), zinc (Zn), copper (Cu), and plasma malondialdehyde (MDA) as well as erythrocyte glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) values were measured in the patients and controls. Results: Plasma MDA values of the patient group were significantly ( p < 0.001) higher than those in control. Serum Zn, Se, and erythrocyte GSH-Px values of the patient group are significantly ( p < 0.001) lower than those in control, although there is no statistical difference in Cu and SOD values. Conclusion: Plasma MDA, erythrocyte GSH-Px, and trace elements Zn and Se may play an important role in the pathogenesis of intractable epilepsy in children.